2020
DOI: 10.3390/ijerph17093014
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Socioeconomic Factors on Spatiotemporal Patterns of PM2.5 Concentration in Beijing–Tianjin–Hebei Region and Surrounding Areas

Abstract: The study investigated the spatiotemporal evolution of PM2.5 concentration in the Beijing–Tianjin–Hebei region and surrounding areas during 2015–2017, and then analyzed its socioeconomic determinants. First, an estimation model considering spatiotemporal heterogeneous relationships was developed to accurately estimate the spatial distribution of PM2.5 concentration. Additionally, socioeconomic determinants of PM2.5 concentration were analyzed using a spatial panel Dubin model, which aimed to improve the robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Natural factors, such as temperature, wind speed, air humidity, topography, and the underlying surface, are notable examples. Moreover, socioeconomic factors include population density [32], GDP per capita [33], industrial structure [26], energy consumption [34], and other issues such as use of fireworks and firecrackers [22,23,35,36]. Land use patterns can also be critical.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural factors, such as temperature, wind speed, air humidity, topography, and the underlying surface, are notable examples. Moreover, socioeconomic factors include population density [32], GDP per capita [33], industrial structure [26], energy consumption [34], and other issues such as use of fireworks and firecrackers [22,23,35,36]. Land use patterns can also be critical.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In reviewing the literature, focusing on the scalability of research, recent scholarship seems to fall into three categories: the national scale [34,52], urban agglomerations [32,33], and provincial or city scale [50,53]. It is now understood that relevant research on PM 2.5 pollution characteristics and source analyses in China is mainly concentrated on the regions of Beijing-Tianjin-Hebei, the Yangtze River Delta, the Pearl River Delta and Central Plains urban agglomerations, and other complex and severely polluted areas [32,33,51,53,54]. Some Chinese regions maintain or enhance their competitiveness in attracting FDI at the expense of the natural environment [55].…”
Section: Literature Reviewmentioning
confidence: 99%
“…PM 2.5 pollution is not only a natural phenomenon influenced by meteorological conditions, but is also influenced by severe anthropogenic emissions [ 8 , 22 , 40 , 41 , 47 , 48 ]. Thus, the relationship between PM 2.5 meteorological variables is not constant but is changing over time [ 24 ]. Therefore, we assumed that the developed regression model trained based on the PM 2.5 and meteorological data collected from a specific period represents the relationship between them under the emission scenario of the specific period.…”
Section: Methodsmentioning
confidence: 99%
“…These studies demonstrated that on an economic development level, urbanization level, coal consumption, motor vehicles, and population size are key influencing factors of PM 2.5 . Wang et al used a spatial panel Dubin model to investigate the relationship between PM 2.5 and six socioeconomic factors during 2015~2017 in Beijing–Tianjin–Hebei (BTH) [ 24 ]. It was found that the urbanization rate has a negative effect on PM 2.5 , which may be due to the stricter environmental regulations than before.…”
Section: Introductionmentioning
confidence: 99%
“…For this local variation GWR model, local variable parameters can be more accurately used to reflect the spatial variation and difference, and a continuous parameter value surface is generated (Engel-Cox et al, 2004;Hu et al, 2013). GWR is a regression model for testing continuous surface spatial variation and non-stationary problems of regression parameter values on a regional scale (Wang et al, 2020). Although AOD is the most significant indicator of PM2.5 concentration, PM2.5 concentration is also significantly affected by temperature, precipitation and other climatic factors (Lv and Li, 2018).…”
Section: Geographically Weighted Regression Modelmentioning
confidence: 99%